Fostering Students’ Reading Comprehension through Visualization Strategy - Eviyanti Eviyanti; Afrillia Anggreni; Andi Patmasari; Sriati Usman (MASI Mandiri Edukasi, 2025)
Comprehending explicitly stated information in reading passages remains a persistent challenge for many junior high school students, often hindering their ability to understand texts at the literal level, which forms the foundation for higher-order comprehension skills. Therefore, this study aims to determine whether the visualization strategy significantly improves literal reading comprehension among EFL students. The research was conducted at SMP Negeri 20 Palu using a quasi-experimental design. The population consisted of 105 eighth-grade students from classes VIII A, VIII B, VIII C, and VIII D, with class VIII C assigned as the experimental group and class VIII B as the control group through random sampling. Pre-tests and post-tests were administered to collect data. The findings revealed that the experimental group achieved a higher mean score (78) than the control group (63) in the post-test, and the statistical analysis showed a significance value of p < 0.05, indicating that the visualization strategy effectively enhanced students’ reading comprehension, particularly in understanding literal information in descriptive texts. These findings suggest that visualization strategies can be integrated into EFL instruction to improve students’ engagement, comprehension, and overall learning experience.